A Deep Dive into the Complex Chemical Mixture and Toxicity of Tire Wear Particle Leachate in Fathead Minnow. (2nd August 2021) - Chibwe, Leah; Parrott, Joanne L.; Shires, Kallie; Khan, Hufsa; Clarence, Stacey; Lavalle, Christine; Sullivan, Cheryl; O'Brien, Anna M.; De Silva, Amila O.; Muir, Derek C.G.; Rochman, Chelsea M.
Abstract: The ecological impact of tire wear particles in aquatic ecosystems is a growing environmental concern. We combined toxicity testing, using fathead minnow (Pimephales promelas ) embryos, with nontarget high‐resolution liquid chromatography Orbitrap mass spectrometry to characterize the toxicity and chemical mixture of organic chemicals associated with tire particle leachates. We assessed: 1) exposure to tire particle leachates after leaching for 1‐, 3‐, and 10‐d; and 2) the effect of the presence and absence of small tire particulates in the leachates. We observed a decrease in embryonic heart rates, hatching success, and lengths, as well as an increase in the number of embryos with severe deformities and diminished eye and body pigmentation, after exposure to the leachates. Overall, there was a pattern whereby we observed more toxicity in the 10‐d leachates, and greater toxicity in unfiltered leachates. Redundancy analysis showed that several benzothiazoles and aryl‐amines were correlated with the toxic effects observed in the embryos. These included benzothiazole, 2‐aminobenzothiazole, 2‐mercaptobenzothiazole, N, N′‐diphenylguanidine, and N, N′‐diphenylurea. However, many other chemicals characterized as unknowns are likely to also play a key role in the adverse effects observed. Our study provides insight into the types of chemicals likely to be important toxicological drivers in tire leachates, and improves our understanding of the ecotoxicological impacts of tire wear particles. Environ Toxicol Chem 2022;41:1144–1153. © 2021 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC. Abstract : Redundancy analysis (RDA) shows positive correlations between chemicals benzothiazoles and aryl‐amines in tire leachates, and increased hatch severity and lack of pigmentation in fathead minnow embryos. OHBT = hydroxybenzothiazole; PBI = 3‐phenyl‐1, 3‐benzothiazol‐2‐imine; NHBT = 2‐aminobenzothiazole; MeSBT = 2‐(methylthio)benzothiazole; MBT = 2‐mercaptobenzothiazole; DPG = N, N′‐diphenylguanidine; CPU = cyclohexyl‐3‐phenylurea; DHU = N, N′‐dicyclohexylurea; DPU = N, N′‐diphenylurea; DHPA = 4, 5‐diphenyl‐1H‐pyrazole‐3‐amine; DHA = dicyclohexylamine; HM = hexa(methoxymethyl)melamine; ABZ = 3‐aminobenzamide; BT = benzothiazole; ACT = acetoacetanilide; TMQ = 1, 2‐Dihydro‐2, 2, 4‐trimethylquinoline; ACR = acridene.